Integrating community gardens into public parks: An innovative approach for providing ecosystem services in urban areas - Middle, Isaac; Dzidic, Peta; Buckley, Amma; Bennett, Dawn; Tye, Marian; Jones, Roy (Elsevier, 2014)
When planned coherently, urban green spaces have the potential to provide cities with a range of unique ecosystem services that support ecosystem and human health. This paper draws on existing green space planning literature to argue that the integration of community gardens into standardised and previously under-utilised public park landscapes represents an innovative approach to providing ecosystem services. Particular focus is given to the challenges facing green space planning in Perth, Western Australia. At an individual level, community gardens provide a venue for an alternative and more accessible form of physical activity – gardening – and a restorative park environment that is a more attractive destination for neighbourhood walking. At the community level, gardens can facilitate bridging interactions between different social groups, whilst providing opportunities for local residents to participate actively in green space planning processes. Perhaps most importantly, community gardens can provide unique opportunities for environmental education that lead to enhanced local ecological outcomes. The paper concludes with a brief overview of the main challenges likely to be faced with this integration, and some strategies that may allow them to be overcome. It is hoped this paper will provide a background for future case studies, and a catalyst for increasing integration between formal green space planning and community garden development.